Gambaran kejadian postoperative nausea vomiting (PONV) pada pasien general dan regional anestesi - Apriyanti, Meli; Sukmaningtyas, Wilis; Safitri, Maya (Holistik Jurnal Kesehatan, 2025)
Background: Postoperative nausea and vomiting (PONV) is a common complication after anesthetic procedures, both general and regional. This condition can cause discomfort, prolong recovery time, and increase healthcare costs. Purpose: To determine the incidence of postoperative nausea and vomiting (PONV) in patients undergoing surgery under general and regional anesthesia. Method: This was a quantitative descriptive study with a cross-sectional approach. The sample consisted of 75 patients undergoing surgery under general or regional anesthesia. Data were collected through observation and questionnaires regarding patient characteristics and the incidence of PONV within 24 hours after surgery. Results: Most respondents were aged 26–45 years (34.7%), predominantly female (62.7%), undergoing major surgery (77.3%) lasting 30–60 minutes (89.3%), and were non-smokers (73.3%). PONV occurred in 39 respondents (52.0%). Regional anesthesia was the most commonly used type of anesthesia (50.7%). Conclusion: PONV occurs more frequently in patients undergoing surgery under general anesthesia compared to patients undergoing regional anesthesia. This may be due to various factors, such as age, gender, type of surgery, duration of surgery, smoking history, and type of anesthesia. Suggestion: More effective prevention and management of PONV is needed, especially in patients undergoing general anesthesia, through the administration of prophylactic antiemetics and preoperative education.   Keywords: Anesthesia; General; Postoperative Nausea and Vomiting (PONV); Regional.   Pendahuluan: Postoperative Nausea and Vomiting (PONV) merupakan komplikasi umum setelah prosedur anestesi, baik general maupun regional. Kondisi ini dapat menyebabkan ketidaknyamanan, memperpanjang waktu pemulihan, dan meningkatkan biaya perawatan. Tujuan: Untuk mengetahui gambaran kejadian postoperative nausea and vomiting (PONV) pada pasien yang menjalani operasi dengan general anestesi dan regional anestesi. Metode: Penelitian desain deskriptif kuantitatif dengan pendekatan cross-sectional. Sampel terdiri dari 75 pasien yang menjalani operasi dengan general atau regional anestesi. Data dikumpulkan melalui observasi dan kuesioner mengenai karakteristik pasien serta kejadian PONV dalam 24 jam pascaoperasi. Hasil: Sebagian besar responden berusia 26–45 tahun (34.7%), mayoritas berjenis kelamin perempuan (62.7%), menjalani bedah mayor (77.3%) dengan durasi operasi 30–60 menit (89.3%), dan tidak merokok (73.3%). Kejadian PONV terjadi pada 39 responden (52.0%). Regional anestesi merupakan jenis anestesi yang paling banyak digunakan (50.7%). Simpulan: Kejadian PONV lebih banyak terjadi pada pasien yang menjalani operasi dengan general anestesi dibandingkan regional anestesi. Hal ini dapat disebabkan karena berbagai faktor, seperti faktor usia, jenis kelamin, jenis operasi, lama pembedahan, riwayat perokok, dan jenis anestesi. Saran: Diperlukan upaya pencegahan dan penanganan PONV yang lebih efektif, terutama bagi pasien dengan general anestesi, melalui pemberian antiemetik profilaksis dan edukasi praoperatif.   Kata Kunci: Anestesi; General; Post Operative Nausea and Vomiting (PONV); Regional.